Comparative Analysis of Child Inheritance with Siblings (Classical Fiqh & Compilation of Islamic Law) - Athoillah, Mohamad (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2024)
In Indonesia, the prevailing legal system is a plural legal system, namely customary law, Islamic law, and Western (continental) law, where the law has binding force because it is realised in the form of laws and the principle of legality. Customary law is the oldest law that has been in force since Indonesian society existed, although it was only recognised as a legal system in the early 20th century. The purpose of this study is to analyse the meaning of the words ‘walad’ and ‘ikhwah’ and their interpretations according to scholars/mufassir, as well as to explain the differences in scholarly views regarding the understanding of the word ‘walad’ in QS. al-Nisa/4:11, 12, and 176. This research is a comparative research, which compares one or more variables between two or more subjects at different times to find a cause-and-effect relationship. The variables compared in this study are the inheritance of children with siblings in classical Fiqh Mawaris and in the Compilation of Islamic Law (KHI). The difference of opinion regarding the inheritance of children and siblings is caused by the use of the terms walad and khwah, where the majority of scholars agree that walad in QS. Al-Nisa/4:11 and 12 includes both sons and daughters, but in QS. Al-Nisa/4:176 only refers to sons. In the Compilation of Islamic Law (KHI), walad includes both genders, which can close the inheritance rights of the deceased's siblings, while the category of ashabah recognised by Sunni scholars is not fully applied in the inheritance system in Indonesia.